Strengthening the resilience of vulnerable communities: Results from a quasi‑experimental impact evaluation in coastal Bangladesh - Béné, Christophe; Haque, Mahfuzul A.B.M. (Springer, 2022)
At present, no clear consensus exists on how to assess resilience interventions in the field. In this paper we propose to measure the impact of the ECOFISH project, the objective of which was to strengthen the resilience of local fishing communities affected by recurrent crises in Bangladesh. The evaluation was based on a difference-in-difference (DiD) framework. The DiD analysis indicates that households who benefited from ECOFISH have a higher propensity to adopt positive responses than non-beneficiaries when hit by a shock. Those beneficiaries also report a statistically higher recovery rate (resilience). The analysis indicates however that the project did not manage to reduce the propensity of households to engage in detrimental coping strategies and that the long-term food and nutritional security of the beneficiaries has not yet visibly improved compared to the control group. Those different results are discussed in the light of the wider literature on resilience evaluation.